PENGARUH HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI PAKAIAN DI H&M SUMMARECON MALL BEKASI - Rofiyta Miladiyah; Neng Siti Komariah (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
This research aims to determine simultaneously and partially the independent variables, namely price, brand image and product quality, the dependent variable is buying interest. The method used in this study is a quantitative method, which in this study uses purposive sampling calculations with the hair formula. The population in this study were all consumers of H&M clothing with a sample of 95 respondents. Based on the results of the study, in the partial test (T) the price variable has a partial negative effect on Purchase Intention with a value of 0.534 (t-count) < 1.66140 (t-table) with a significant value of 0.594 > 0.05. Brand Image variable has a negative effect on Purchase Intention with a value (t-count) of 1.461 < 1.66140 (t-table) with a significant value of 0.148 > 0.05 and Product Quality Variable has a partial positive effect on Purchase Intention with a value of 5.409 (t-count) > 1.66140 (t-table) with a significant value of 0.000 <0.05. Furthermore, in the simultaneous test (f) the price, brand image and product quality variables simultaneously have a positive effect on the purchase intention variable with a value (f-count) of 34.195 > 2.70 (f-table) with a significant value of 0.000 <0.05. Then the determination test (R2) resulted in a correlation between the three variables Price (X1), Brand Image (X2) and Product Quality (X3) on Purchase Intention (Y) of 52.8%.